Self-reflection, sense of agency, and underlying neural correlates: A pilot study - Kurusetti Vinay Gupta; Jyotiranjan Beuria; Lokeswara Kumar Vijanapalli; Amit Sethi; Laxmidhar Behera (PLoS ONE, 2025)
The sense of agency refers to the feeling of controlling one’s actions to influence the outside world. The association between an individual’s sense of agency and their psychological or behavioral characteristics has been extensively studied in recent years. However, the direct impact of self-reflection, a key strategy for modulating one’s cognitive state, on implicit measures of agency remains largely unexplored. We employed a between-subjects experimental design, to investigate the effect of two types of self-reflection - self-centered and selfless upon the implicit sense of agency. Additionally, we explored neural activity during self-reflection to see if there are any correlations with the sense of agency. Agency was measured using intentional time binding experiments, assessing the ability to perceive event sequences over time. Results indicated that self-centered reflection enhances time binding and agency, while selfless reflection has the opposite effect. Traditional spectral density measures and topological data analysis revealed distinct neural patterns for each type of reflection. Specifically, selfless reflection showed increased Hodge spectral entropy and persistent entropy compared to self-centered and control groups, indicating greater topological complexity in EEG time series. A significant negative correlation between second-order Hodge spectral entropy and time binding effect was observed. The study provided initial evidence that topological EEG features could serve as potential neural markers of the sense of agency modulated through self-reflection.